The Use of Probiotics in Preterm Infants - Hye Won Park (Korean Society of Neonatology, 2022)
Probiotics are live microorganisms that positively affect host health by altering the composition of the host microbiota. Gastrointestinal dysbiosis refers to adverse alterations of the intestinal flora and is associated with several diseases, including necrotizing enterocolitis, late-onset sepsis in preterm infants as well as atopic disease, colic, diabetes, and diarrhea in term infants. The risk factors for gastrointestinal dysbiosis are preterm birth, cesarean section delivery, and formula feeding, in contrast to term birth infants, vaginal delivery and breast milk feeding. Probiotics have been used to restore synbiosis in infants with gastrointestinal dysbiosis. Probiotics inhibit colonization of pathogenic bacteria in the gastrointestinal tract, thereby improving the barrier function of the gastrointestinal tract, and the immune function. In preterm infants, probiotics reduce mortality as well as rates of necrotizing enterocolitis and late-onset sepsis. The combined use of probiotics such as Lactobacillus and Bifidobacterium and the combination of probiotics with prebiotics yield better outcomes in the prevention of necrotizing enterocolitis than those achieved with a single pro- or prebiotic strain. However, the routine use of probiotics has been hindered by the lack of pharmaceutical-quality products, and a definite effect has yet to be demonstrated in preterm infants with a birth weight <1,000 g. Therefore, to reduce the risk of necrotizing enterocolitis in preterm infants, probiotics should be provided along with breast milk and other strategies aimed at preventing gastrointestinal dysbiosis.